A novel uromodulin mutation in autosomal dominant tubulointerstitial kidney disease: a pedigree-based study and literature review. (15th October 2018) - Lin, Ziqiang; Yang, Juan; Liu, Hong; Cai, Dan; An, Zhenmei; Yu, Yerong; Chen, Tao
Abstract: Autosomal dominant tubulointerstitial kidney disease caused by mutations in uromodulin gene (ADTKD- UMOD ) is a spectrum of hereditary renal disorders, characterized by early-onset hyperuricemia, gout and progressive nephropathy. This study presented a novel UMOD mutation in an ADTKD pedigree and reviewed studies in Chinese population. The index patient is a 16-year-old girl with hypertension, hyperuricemia and normal serum creatinine level. Four affected and six unaffected members were available for genetic screen. The mutation analysis was performed by next-generation sequencing and direct sequencing. A literature research was conducted to review Chinese ADTKD- UMOD cases. MEDLINE and Chinese Biomedicine Databases were searched with 'uromodulin', 'juvenile gout' and their related terms. Genetic sequencing revealed a de novo mutation within exon 3 (Cys223Gly), which was co-segregating with phenotype in this pedigree. In the review, four studies and our study involving a total of 67 ADTKD patients from 11 families were identified. Of these patients, 27 were confirmed to carry UMOD mutations. Mutations occurred in exon 3 were commonly observed, while mutations within exon 4, 5 and 9 occurred less frequently in Chinese ADTKD- UMOD cases. Among these cases, median age of symptom onset was 26.5 years, median age of end-stage renal diseases (ESRD) or death by ESRD was 41.9 years without renal replacement treatment. Phenotype caused by mutations in D8C domain seemed to be severe than those in GPI domain. Compared with patients of other race, Chinese ADTKD-UMOD patients advanced more aggressively to ESRD.